Appendix A and Appendix B. Supplementary data for Automated astronaut traverses with minimum metabolic workload: Accessing permanently shadowed regions near the lunar south pole - Peña-Asensio, Eloy; Sutherland, Jennifer; Tripathi, Prateek; Mason, Kashauna; Goodwin, Arthur; Bickel, Valentin T.; Kring, David A. (Elsevier, 2024)
Appendix A: Fig. A1. Example spread of the traverse and descent, as well as a 2D plot with elevation contours, a 3D plot using 2 m/pixel NAC images and 5 m/pixel LOLA DEM, and a histogram of the distance traveled as a function of the slope. Fig. A2. Example of the tables associated with each traverse with general values calculated, and the 2 m/pixel NAC image and a detailed 2D map of the host crater. Fig. A3. Example of the tables associated with each PSR optimal descent with general values calculated, and a detailed 2D and 3D image of the host crater. Appendix B. Supplementary data: Multimedia component 1. Multimedia component 2. Multimedia component 3. Peer reviewed